Sollten Förderentscheidungen partiell durch Lotterien ersetzt werden? Grundlagen, Konzeption und Evaluationsdesign am Beispiel des Förderinitiative `Experiment!` der Volkswagen Stiftung - Mutz, Rüdiger; Wolbring, Tobias; Daniel, Hans Dieter (Zeitschrift für Evaluation, 2023)
In view of the criticism of the peer review process, some research funding organi-zations have introduced a lottery element into the selection procedures for selected funding initiatives. The aim of this conceptual paper is to discuss the lottery procedure as an element of a decision-making process in research funding, using the funding initiative “Experiment!“ of the Volkswagen Foundation (VWS) as an example. First, the general principles of lotteries will be presented, from four perspectives: the procedure, statistics, economics, and social psy-chology. These general considerations on lotteries will serve as a foil to review the literature on ‘lotteries in research funding’. As an example, the funding initiative “Experiment!” of the VWS will be presented and a design for the ex-post evaluation of the effects of the lottery element in the selection process will be developed. Finally, recommendations for the impact evaluation of such modified selection procedures will be formulated.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Doubly Randomized Preference Trial; Lottery; Program Evaluation; Research Funding